16-(2x-4)-(5x-3x+2)=-4x-(-8x+2)

Simple and best practice solution for 16-(2x-4)-(5x-3x+2)=-4x-(-8x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16-(2x-4)-(5x-3x+2)=-4x-(-8x+2) equation:



16-(2x-4)-(5x-3x+2)=-4x-(-8x+2)
We move all terms to the left:
16-(2x-4)-(5x-3x+2)-(-4x-(-8x+2))=0
We add all the numbers together, and all the variables
-(2x-4)-(2x+2)-(-4x-(-8x+2))+16=0
We get rid of parentheses
-2x-2x-(-4x-(-8x+2))+4-2+16=0
We calculate terms in parentheses: -(-4x-(-8x+2)), so:
-4x-(-8x+2)
We get rid of parentheses
-4x+8x-2
We add all the numbers together, and all the variables
4x-2
Back to the equation:
-(4x-2)
We add all the numbers together, and all the variables
-4x-(4x-2)+18=0
We get rid of parentheses
-4x-4x+2+18=0
We add all the numbers together, and all the variables
-8x+20=0
We move all terms containing x to the left, all other terms to the right
-8x=-20
x=-20/-8
x=2+1/2

See similar equations:

| 7x²-70=0 | | 16+3s-9=5s-17 | | (3x)/2+(2x/3)=(1+3x)/2 | | x+8+24+136=180 | | 16+3s-9=5s | | 25+x+75=180 | | 5x+2=9x+5 | | x+75+25=180 | | 56+7y=-14 | | 56+7y=0-14 | | 0,5x^2+2x=0 | | -8t=2t+40 | | 24+y=18 | | 0.00109=(x+0.10)(x) | | 4x^2=-x-5 | | 70+60+51x-1=180 | | 5x+7(-3x-5)=13 | | 2+6x+110=180 | | -3f+9=-7f-15 | | 8x-10=(3/2)(4x-6) | | 2x+4(3x-4)=3x+12 | | x=1225 | | 8x-10=((3/2))(4x-6) | | 4x+3+147=180 | | 17+3m=-1 | | 5x+15=×+25 | | 2x+1+129=180 | | 37=3(1+5a)=88 | | 49+7y=-14 | | P(10)=0.80n+5.50 | | -24+6y-6y=3 | | 8^5x-2=1/4 |

Equations solver categories